Conspicuous consumption and social segmentation (2003)
This paper develops the idea that conspicuous consumption has an impact on social segmentation, i.e., on the partition of the society into communities. Even though agents do not value conspicuous goods per se, they are competing in a signalling race in order to benefit from social interactions within a community. First, we study the equilibria of this model defining the optimal strategies and the equilibrium partition that characterizes pooling and separating equilibria. In a second step, as conspicuous consumption is a pure waste of money, we study a possible Pareto–improving taxation policy.